Components of the Approach and Design of the Arabic Language Learning System Planning - Rakhmad Agung Hidayatullah; Nanang Dwi Purwanto; Saiful Aziz; Amir Reza Kusuma (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Arabic language learning holds a highly strategic position, particularly in the context of Islamic education, linguistic studies, and the needs of global communication. The success of this learning is largely determined by the appropriate selection of methods, approaches, and learning system design. This demonstrates that learning planning is a key factor in achieving learning objectives effectively and efficiently. Along with developments in educational theory and language learning technology, Arabic language learning planning needs to be systematically designed, taking into account the integration of various components, such as objectives, materials, methods, media, and evaluation. From a modern perspective, language learning methods are not merely understood as teaching techniques but encompass the relationship between approaches, designs, and procedures that are integrated within a learning system. The results provide an in-depth analysis of the components of approaches in Arabic language learning and the design of effective learning system planning. Furthermore, this research aims to identify learning strategies that can improve student learning outcomes and contribute to improving the quality of Arabic language teaching in various educational institutions.